Prospect Photographie. - Frankfurter Kunstverein, Frankfurt; Steinernes Haus am Römerberg, Frankfurt am Main (Frankfurt : Frankfurter Kunstverein, 1989)
Avedon, Richard ; Baldessari, John ; Blume, Bernhard Johannes ; Boltanski, Christian ; Collin-Thiébaut, Gérard ; Cooper, Thomas Joshua ; Coplans, John ; Evergon ; Faucon, Bernhard ; Förg, Günther ; Fuss, Adam ; Garnet, Eldon ; Head, Tim ; Hilliard, John ; Jaar, Alfredo ; etc.
Prospect Photographie, Frankfurter Kunstverein, Steinernes Haus am Römerberg, Frankfurt, 13.10. - 26.11.1989
boek